PARENT’S MOTIVATION IN FORMAL EDUCATION AT RESTRICTION AREA (Case Study in People of Keter Laut Island Regency of Bintan) - Miswanto, Miswanto; Utari, Diah Siti; Pramono, Dwikhy Anindito (LPPM Universitas PGRI Sumatera Barat, 2018)
Education is a necessity for everyone. By education, people will clever and can solve both social and economy problems in their family. Because of that reason, parent’s involvement in children education can be interpreted as indicator how their perception about education. Most of people in Keter Laut Island have profession as fisherman which depend on yield of ocean’s catch. It makes parent sometime forget their duty as first agent of socialization in family and also forget right of the children. It a must for parent to make a life and be responsible to their family, not involve children to work, especially for whom need education and lesson at school. The goal of this research is to know how parent’s motivation in formal education for children in Keter Laut Island. The method of this research is descriptive qualitative, which use both of interpretative and naturalistic approach to the main study (Subject of Matter). The population of this research is parents who have children attend school. The sample is taken by Saturated Sampling technique. There are 20 people as the sample. From this research, all parents in Keter Laut Island want their children have a better education because by education, intelligence will improve and of course it will change people’s life in Keter Laut Island include their economy sector. Beside of that, parents also do not want their children have same destiny as their parents who have profession as a fisherman while their income just enough barely to live on.